Perancangan Ulang Alat Pemotong Kerupuk Manggar Guna Meningkatkan Kapasitas Pemotongan dan Efisiensi Produksi - Amela, Sarah Yunita; Purnama, Jaka (Fakultas Teknik UMRI, 2024)
Terik Surya is an industry that produces raw weed. The kinds of debris that are produced are mangroves and roses. In the process of cutting mangroves, there are some difficulties in cutting with a mangrove cutting tool. The only knife eye on this moss cutting machine is only three pieces with workers alternating when inserting the moss to be cut. This high-dimensional mangroves cutting tool is not as ergonomic as it should be. From the results of anthropometric data processing that has been performed on 5 workforce cutting the debris obtained the width of the device 72.8 Cm, the height of the instrument 90 Cm and the length of holding 94,5 Cm. The redesign of this mangroves cutting machine has experienced an increase in capacity that was initially 1.4 kg per minute to 2.5 kg a minute.